2019
DOI: 10.1002/pon.5041
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on women's values and preferences concerning breast cancer screening and diagnostic services

Abstract: Background There is still lack of consensus on the benefit‐harm balance of breast cancer screening. In this scenario, women's values and preferences are crucial for developing health‐related recommendations. In the context of the European Commission Initiative on Breast Cancer, we conducted a systematic review to inform the European Breast Guidelines. Methods We searched Medline and included primary studies assessing women's values and preferences regarding breast cancer screening and diagnosis decision making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
(85 reference statements)
4
35
0
3
Order By: Relevance
“…18,22 Nevertheless, the reviews agreed that untargeted mass invitations (including social networks and mass media) had no effect on screening participation, 13,20,34 while recommendations from healthcare providers were important. 14,19,35 [14][15][16]36 Situational factors/cues to action Risk-factor questionnaires No or limited effect Two reviews 14,26 Fixed appointment with any invitation approach Positive Four reviews 13,14,18,22 Reminder letters or invitation follow-ups Positive Eight reviews 8,13,14,18,19,22,28 Regarding education-related interventions, the reviews based on both trials and observational evidence showed a positive impact of telephone counselling, 8,14,28,29 face-toface counselling, 18,20,22,28 and educational home visits 14,29 on uptake of screening mammography. However, the last two types of intervention were non-superior to simple calls or letters.…”
Section: Factors Contributing To Variability In Bcs Participation Andmentioning
confidence: 99%
“…18,22 Nevertheless, the reviews agreed that untargeted mass invitations (including social networks and mass media) had no effect on screening participation, 13,20,34 while recommendations from healthcare providers were important. 14,19,35 [14][15][16]36 Situational factors/cues to action Risk-factor questionnaires No or limited effect Two reviews 14,26 Fixed appointment with any invitation approach Positive Four reviews 13,14,18,22 Reminder letters or invitation follow-ups Positive Eight reviews 8,13,14,18,19,22,28 Regarding education-related interventions, the reviews based on both trials and observational evidence showed a positive impact of telephone counselling, 8,14,28,29 face-toface counselling, 18,20,22,28 and educational home visits 14,29 on uptake of screening mammography. However, the last two types of intervention were non-superior to simple calls or letters.…”
Section: Factors Contributing To Variability In Bcs Participation Andmentioning
confidence: 99%
“…These challenges have even shown to exist in patients who have experienced multiple colonoscopies (33). Although planning in everyday life due to participation have also shown to be challenging in other screening settings like breast cancer screening (34,35), preparation for colonoscopy have shown to interfere with everyday activities for a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…Image-guided biopsies are considered safe irrespective of the method used. Proven is a certain psychological harm in terms of increased anxiety and associated symptoms [24]. Despite this, psychooncological research data demonstrate that women are actually willing to accept both the direct harms by recalls and unnecessary biopsies and the possibility of overdiagnosis for the prospect of an earlier diagnosis [24].…”
Section: Psychological and Physical Harms Of Invasive Diagnostic Procmentioning
confidence: 99%
“…In case of doubt, we should consider the opinion of those affected. Eligible women themselves, being those that are subject to both risks and benefits, generally are in favour of screening despite acknowledging the risk [24]. While one could argue that the concept of overdiagnosis is difficult to convey on an individual level and that it is limited understanding of the associated risks that brings women to support screening, such arguments are elitist in nature and deeper discussed in the context of democracy in [32].…”
Section: Overdiagnosismentioning
confidence: 99%